Motivational Interviewing and Oral Heath: what the evidence says - Carriconde, Beatriz; Faustino Silva, Daniel Demetrio (Journal of Oral Research, 2019)
Motivational Interviewing is an approach to health that is almost the opposite of the traditional format applied by different health care professionals. In oral health, in particular, in which behavior is so decisive in the successful treatment of the most prevalent diseases, breaking the dominance of prescriptive, judgmental and counselling-based practices is paramount. We cannot restrict the advancement of current knowledge to the microbiological and technical levels of clinical practice; discussions must be extended to include how to promote healthcare and unsettle professionals secure in their authoritarian and hierarchical approach, paving the way for a line of thought that considers the relationships we establish with our patients.